Coworking Space Interior Design with Rattan Theme in Trangsan Village of Sukoharjo - Pantini, Retno; Prasetyo, Ersnathan Budi; Mumpuni, Primastiti Wening (Pendhapa, 2023)
The interior design of a coworking space with a rattan theme in Trangsan Sukoharjo Village functions as a means of renting workspaces that are used jointly and openly with other users with flexible time usage. This design aims to create an interior design for a coworking space in Sukoharjo that can meet the needs of activities that are safe, comfortable and create a productive atmosphere. This design adopted several stages of the design process proposed by Kurtz. Kurtz's model of programming is programming on the qualitative rather than quantitative side. The basis of the design used is the function, ergonomics, technical, color, theme and style approaches. This design adopts a Bohemian design style with a rattan theme as the design base. The rattan theme gives a natural impression of the use of rattan characteristics applied to interior elements in the form of furniture, partitions and so on.